(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the effectiveness and safety of endoscopic retrograde laser lithotripsy with a rigid scope in the treatment of ureteral stones in 2020 - 2023. Subjects and methods: Prospective study describing intervention, performed on 256 patients diagnosed with ureteral stones in various locations, endoscopic retrograde laser lithotripsy at Military Hospital 91 from February 2020 to June 2023. Results: In the study, there were 49.6% right ureteral stones, 48.6% left ureteral stones, 2% bilateral ureteral stones, 33.2% upper 1/3 stones, 30.2% middle 1/3 stones, 4%, stones in the lower third 27.3%. The average size of the stones is 13.1mm, 90.2% of the stones are radiopaque, and 9.8% of the stones are not clearly visible. Stones cause ureteral obstruction in hydronephrosis level I in 18.3%, hydronephrosis level II in 72.6%, hydronephrosis level III in 8.9% and 0.2% of non-hydronephrosis patients; Average lithotripsy time is 36.2 minutes, 2.34% of stones cannot be reached; Indications for JJ tube placement after stone intervention account for 100%. Conclusion: Retrograde ureteroscopy with a rigid scope and laser diffuser source has high value in treating ureteral stones, with 96% success. The method is safe, highly effective, shortens treatment days, and restores health early.